Breaking into the Fulcrum Arena: A Concept Paper Looking Beyond Next Generation LMS - Hai-Jew, Shalin (My University, 2010)
In the spirit of futurist probes into what a nextgen learning management system (LMS) may look like, the author uses a scifi scenario to touch on some distant possibilities. This fictional work follows J4 in his quest to break into the Fulcrum Arena and emerge with the information and strategic relationships he needs to achieve mysterious aims. This story envisions a learning space that integrates various databases, global positioning systems (GPS), and other technologies into an integrated digital enclosure. It focuses on informational elites, those who have the rawest and freshest information, vs. those who get processed versions through public channels. Here, identities are persistent and coalesced through information collected by ‘bots. The learning is all strategic, it’s immersive, and it directly applies to the lived world.
Keywords: Next generation learning management system; Future learning; Forecasting; Immersive learning